2021
DOI: 10.15586/ijfs.v33i4.2123
|View full text |Cite
|
Sign up to set email alerts
|

Goldenberry (Physalis peruviana L.) seed oil: press extraction, optimization, characterization, and oxidative stability

Abstract: In order to optimize the screw-press extraction conditions of oil from goldenberry (Physalis peruviana L.) seeds obtained from nectar processing waste, a face centered design was applied. The oil was extracted at different temperatures (60, 80, and 100°C) and seed moisture contents (8, 10, and 12%). Oil recovery (OR) increased and residual oil in the cake decreased significantly as moisture content and temperature were reduced; oil moisture and volatile matter as well as acid value, K232, K268, and p-anisidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…(2021) and Ugarte‐Espinoza et al . (2021), but closer to that reported for fruit peel in the same Popova et al . (2021) study.…”
Section: Resultssupporting
confidence: 89%
“…(2021) and Ugarte‐Espinoza et al . (2021), but closer to that reported for fruit peel in the same Popova et al . (2021) study.…”
Section: Resultssupporting
confidence: 89%
“…UV absorption changes at 232 and 268 nm, measured as K232 and K268, provide insights on the degree of oxidative damage of lipids [ 60 ]. It was found that K232 is strongly correlated with the level of conjugated dienes (CDs) produced as a consequence of the primary oxidation process of polyunsaturated fatty acids, while K268 is more closely linked to the presence of conjugated trienes (CTs) and carbonyl compounds formed in response to secondary lipid oxidation processes [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The friction of the pressed material arises on the surface of the turns, the walls of the perforated cylinder and the friction of the particles among themselves [37]. Also, it is important to take into account the resistance of the mechanism that regulates the size of the outlet opening for the cake (cone, diaphragm, ring) [38]. The friction of the pressed material arises on the surface of the turns, the walls of the perforated cylinder and the friction of the particles among themselves [39].…”
Section: Discussionmentioning
confidence: 99%